Vibrio sp. dhg as a platform for the biorefinery of brown macroalgae - Hyun Gyu Lim; Dong Hun Kwak; Sungwoo Park; Sunghwa Woo; Jae-Seong Yang; Chae Won Kang; Beomhee Kim; Myung Hyun Noh; Sang Woo Seo; Gyoo Yeol Jung (Nature Communications, 2019)
Brown macroalgae is a good candidate feedstock for biorefinery, but the major carbohydrate alginate cannot be digested by current industrial microbes. Here, the authors isolate Vibrio sp. dhg and engineer it to produce value-added biochemicals from alginate using newly developed genetic tools.